Human Liver Stem Cell-Derived Extracellular Vesicles Prevent Aristolochic Acid-Induced Kidney Fibrosis - Kholia, Sharad; Herrera Sanchez, Maria Beatriz; Cedrino, Massimo; Papadimitriou, Elli; Tapparo, Marta; Deregibus, Maria Chiara; Brizzi, Maria Felice; Tetta, Ciro; Camussi, Giovanni (Frontiers in Immunology, 2018)
With limited therapeutic intervention in preventing the progression to end stage renal disease, chronic kidney disease (CKD) remains a global healthcare burden. Aristolochic acid (AA) induced nephropathy is a model of CKD characterised by inflammation, tubular injury and interstitial fibrosis. Human liver stem cell derived extracellular vesicles (HLSC-EVs) have been reported to exhibit therapeutic properties in various disease models including acute kidney injury. In the present study, we aimed to investigate the effects of HLSC-EVs on tubular regeneration and interstitial fibrosis in an AA induced mouse model of CKD. NSG mice were injected with HLSC-EVs three days after administering AA on a weekly basis for four weeks. Mice injected with AA significantly lost weight over the four week period. Deterioration in kidney function was also observed. Histology was performed to evaluate tubular necrosis, interstitial fibrosis, as well as infiltration of inflammatory cells/fibroblasts. Kidneys were also subjected to genetic array analyses to evaluate regulation of microRNAs and fibrotic genes. The effect of HLSC-EVs was also tested in vitro to assess fibrotic gene regulation in fibroblasts co-cultured with AA treated tubular epithelial cells. Histological analyses showed that treatment with HLSC-EVs significantly reduced tubular necrosis, interstitial fibrosis, infiltration of CD45 cells and fibroblasts which were all elevated during AA induced injury. At a molecular level, HLSC-EVs significantly inhibited the upregulation of the fibrotic genes α-Sma, Tgfb1 and Col1a1 in vivo and in vitro. Fibrosis gene array analyses revealed an upregulation of 35 fibrotic genes in AA injured mice. Treatment with HLSC-EVs downregulated 14 fibrotic genes in total, out of which 5 were upregulated in mice injured with AA. Analyses of the total mouse miRnome identified several microRNAs involved in the regulation of fibrotic pathways which were found to be modulated post treatment with HLSC-EVs. These results indicate that HLSC-EVs play a regenerative role in CKD possibly through the regulation of genes and microRNAs that are activated during the progression of the disease.